Visual C# 2005 Recipes A Problem-Solution Approach - Rajan, Rakesh; MacDonald, Matthew; Jones, Allen (Apress : Imprint: Apress, 2006)
Mastering .NET development is as much about understanding the functionality of the .NET Framework as it is about the syntax and grammar of your chosen language. Visual C# 2005 Recipes: A Problem-Solution Approach recognizes this fine balance. This book meets your need for fast, effective solutions to the difficulties you encounter in your coding projects. The recipes included in this book have been chosen and written with emerging pros in mind. The book features an equal balance of code and text. The supplied code gives you everything you need to solve the problem at hand, while the accompanying text provides supporting information. This is a fully up-to-date reference for .NET 2.0 programmers. All code comes as a stand-alone Visual Studio 2005 solution. The book even covers advanced concepts that take you past basic recipe solutions you'll be able to distill entire concepts and theories.